To Study the Treatment Outcome of Various Management Strategies of Liver Abscess: A Prospective Study From A Tertiary Hospital Centre. - Mohammad Kashif; Shabi Ahmad (Asian Journal of Medical Research, 2018)
Background: Liver abscess was found more commonly in men between 18 and 60 years of age but can occur at any age. Approximately 80% were solitary and mainly located in right lobe of liver. The most common presenting clinical symptoms are upper abdominal pain, high-grade fever, nausea, and vomiting. The most common sign is right hypochondrial tenderness frequently with guarding and hepatomegaly. Some patients may present with jaundice and pleural effusion. Percutaneous catheter drainage was most widely used treatment method for liver abscess. Percutaneous needle aspiration also used for treatment of liver abscess, was a simpler, less costly and equally effective mode of treatment. In some patients of amoebic liver abscess associated with secondary bacterial infection and with ruptured liver abscess, surgical drainage had been the traditional mode of treatment. Subjects and Methods: Patients of unruptured liver abscess were randomly allocated into medical management, PCD and PNA groups for comparison. Results: Out of total 60 cases studied, Percutaneous catheter drainage (PCD) was most widely used treatment method in 27 (45%) cases of liver abscess. Percutaneous needle aspiration (PNA) also used for 21 (35%) cases, surgical treatment in 07 (11.67%) cases and only medical management was done in 05 (8.33%) cases of liver abscess. Conclusion: Percutaneous catheter drainage (PCD) was most widely used treatment method for liver abscess patients with 100% success rate and Percutaneous needle aspiration (PNA) was next to PCD with 81% success rate.